Potential of electron beam irradiated hdpe/epr blend as shoes sole - Aliyah, L. Husniyah; Anuar, Hazleen (Ministry of Education Malaysia, 2014)
This study focuses on the mechanical effect of different composition of polymer blend. Polymer blend of high density polyethylene (HDPE) and ethylene propylene rubber (EPR) were selected and varied by three different compositions which are 70:30, 50:50 and 30:70. HDPE-EPR blend is believed to be the best material for sole shoe. In which, HDPE has good flexibility while, EPR can maintain optimum performance at high and low temperature as well as provide better gripping characteristic that suits for insole and outsole sport shoe. On the other hand, the time efficiency of electron beam radiation on these polymer blends helps in improving the croslinking of HDPE-EPR blend. The aim of this paper was to find the optimum composition of electron beam irradiated polymer blends for sole shoes especially in sports application. These irradiated polymer blends were produced by melt blending, underwent compression moulding and then were irradiated by electron beam at 100 kGy/s. Mechanical test of tensile and hardness test were investigated and the morphology of the failure fracture was analysed by field emission scanning electron microscopy (FESEM). The polymer blend with 70% of HDPE and 30% of EPR showed the optimum result of tensile strength, tensile modulus and hardness as well as ductile failure image.